SiGMA: A software framework for integrating advanced mathematical capabilities in serious game development. (October 2016) - Smith, Katherine; Shull, John; Dean, Anthony; Shen, Yuzhong; Michaeli, Jennifer
Highlights: Integration of SiGMA, a toolbox for symbolic mathematics into game engines. Allows for symbolic manipulation and display of complex equations and graphs at runtime. Facilitates the development of serious games for mathematics. SiGMA has been utilized in a series of Precalculus games. Abstract: As games become more popular as an educational tool, an imbalance exists in the number of mathematics games that have been developed when compared to the number of games developed for other fields. Part of the reason for this gap can be attributed to the difficulty of symbolic manipulation and display of complex equations and graphs. To alleviate this, SiGMA, a symbolic toolkit for gaming mathematics, has been developed. This paper discusses the design and implementation of SiGMA, which has been utilized in a series of games developed as part of the Stern2STEM program that strives to assist military veterans on their path toward STEM degrees. This paper also reviews existing mathematics software and tools and presents game examples that utilized the SiGMA toolkit.